Effects of preoperative nutrition on postoperative outcomes in esophageal cancer: a systematic review and meta-analysis. Issue 3 (10th May 2021) - Cao, Yuqin; Han, Dingpei; Zhou, Xiang; Han, Yu; Zhang, Yajie; Li, Hecheng
Summary: Postoperative enteral nutrition has been widely implemented in esophageal cancer, but the efficacy and safety of preoperative nutrition, particularly immune-enhancing nutrition (IEN), remain controversial. This meta-analysis aims to provide a quantitative synthesis of whether preoperative nutrition improves postoperative morbidity and mortality in patients with resectable esophageal cancer. A systematic search was conducted in Medline, Embase, Cochrane, and databases of clinical trials dated up to December 2019. Randomized controlled trials and observational studies comparing postoperative outcomes between esophageal cancer patients with and without preoperative nutritional support were included. Random-effects model was applied in the meta-analysis of primary outcomes (overall complication rate, in-hospital mortality) and secondary outcomes (infectious complication rate, anastomotic leak rate, length of postoperative hospital stay). Complications of feeding tube access and perioperative weight loss were evaluated by qualitative synthesis. Subgroup analyses were performed by stratifying immunonutrition and standard nutrition before surgery. Subgroup analysis of randomized controlled trials alone was also done. A total of 15 studies enrolling 1864 participants were included. The overall meta-analysis found that preoperative nutrition could reduce infectious complications (odds ratio [OR] = 0.51, 95% confidence interval [CI] [0.26, 0.98]; I 2 = 48%) and length of hospital stay (mean difference = −2.10 day, 95% CI [−3.72, −0.47]; I 2 = 78%) after esophagectomy, whereas no significant difference was revealed in the incidence of overall complications (OR = 0.76, 95% CI [0.52, 1.11]; I 2 = 32%), in-hospital mortality (OR = 1.03, 95% CI [0.41, 2.61]; I 2 = 12%), and anastomotic leak (OR = 1.05, 95% CI [0.69, 1.58]; I 2 = 0%). Subgroup of preoperative immunonutrition showed more prominent benefits. The complication rate of feeding tube access was low (1.6–16%). In conclusion, preoperative nutrition is safe in esophageal cancer, but benefits are observed in infectious complication rate and length of stay on a limited scale. IEN holds more advantages over standard nutrition. Randomized trials in the context of nutritional support during neoadjuvant therapy are in demand.